What can we learn from universal Turing machines?. Issue 2 (4th March 2022) - Margenstern, Maurice
Abstract : In the present paper, we construct what we call a pedagogical universal Turing machine. We try to understand which comparisons with biological phenomena can be deduced from its encoding and from its working.